KORELASI PRESTASI PRAKTIK INDUSTRI DAN WAWASAN WIRAUSAHA DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK YPT PURWOREJO TAHUN PELAJARAN 2014/2015 - Windu Jati Prasmoro; Suparmin Suparmin (Jurnal Taman Vokasi, 2015)
The objectives of the study were (1) correlation between industry practice achievement with entrepreneurship interest among the twelfth grade students of TKR program of SMK YPT Purworejo in academic year 2013/2014; (2) correlation between entrepreneurship knowledge with entrepreneurship interest among the twelfth grade students of TKR program of SMK YPT Purworejo in academic year 2013/2014; and (3) correlation between industry practice achievement and entrepreneurship knowledge with entrepreneurship interest among the twelfth grade students of TKR program of SMK YPT Purworejo in academic year 2013/2014.This study was ex-post facto. The population was all of twelfth grade students of TKR program of SMK YPT Purworejo in academic year 2013/2014 consisted of 102. The researcher used random sampling technique to determine the sample of the research. This researcher took the sample randomply with the percentage 71% from the population 102 students, so that the sample was 71% X 102 = 72 students. So, the sample of the research was 72 students. Methods in collecting the data used questionnaire and documentation method. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double correlation.This study shows that (1) there was positive and significant correlation between industry practice achievement with entrepreneurship interest with the score of r obs 0,388 and the score of significance 0,000 < 0,05; (2) there was positive and significant correlation between entrepreneurship knowledge with entrepreneurship interest with the score of r obs 0,492 and the significant score 0,000 < 0,05; and (3) there was positive and significant correlation between industry practice achievement and entrepreneurship knowledge with entrepreneurship interest among the students of twelfth grade students of TKR program of SMK YPT Purworejo in academic year 2013/2014 with the score of 0,609 and the significant level 0,000.